Pattern Propagation Factor of the Earth - L. S. Mettus; V. N. Mikhailov; A. B. Khachaturian (Известия высших учебных заведений России: Радиоэлектроника)
The article is devoted to the pattern propagation factor of the Earth enabling for more precise determination of the radar station visibility range in case there are reflections from underlying surface. The article provides analytical solution in general form taking into account the Earth sphericity. It enables to obtain the results in the wide-band and altitude range of the observed objects by means of computer simulation. The article gives analytical expression for the Earth multiplier under the flat approximation assumption, free of restrictions common for research literature. Besides, the article defines boundaries in which it is permissible to view the Earth as a flat surface. In addition, the article provides examples to illustrate graphical estimate of the error of all approximations both with respect to the general case of the Earth sphericity and relative to each other.